Nanofibrous poly(lactide-co-glycolide) membranes loaded with diamond nanoparticles as promising substrates for bone tissue engineering - Parizek, Martin; Douglas, Timothy E L; Novotna, Katarina; Kromka, Alexander; Brady, Mariea A; Renzing, Andrea; Voss, Eske; Jarosova, Marketa; Palatinus, Lukas; Tesarek, Pavel; Ryparova, Pavla; Lisa, Věra; et al. (International journal of nanomedicine, 2012)
BACKGROUND: Nanofibrous scaffolds loaded with bioactive nanoparticles are promising materials for bone tissue engineering. METHODS: In this study, composite nanofibrous membranes containing a copolymer of L-lactide and glycolide (PLGA) and diamond nanoparticles were fabricated by an electrospinning technique. PLGA was dissolved in a mixture of methylene chloride and dimethyl formamide (2:3) at a concentration of 2.3 wt%, and nanodiamond (ND) powder was added at a concentration of 0.7 wt% (about 23 wt% in dry PLGA). RESULTS: In the composite scaffolds, the ND particles were either arranged like beads in the central part of the fibers or formed clusters protruding from the fibers. In the PLGA-ND membranes, the fibers were thicker (diameter 270 ± 9 nm) than in pure PLGA meshes (diameter 218 ± 4 nm), but the areas of pores among these fibers were smaller than in pure PLGA samples (0.46 ± 0.02 μm(2) versus 1.28 ± 0.09 μm(2) in pure PLGA samples). The PLGA-ND membranes showed higher mechanical resistance, as demonstrated by rupture tests of load and deflection of rupture probe at failure. Both types of membranes enabled the attachment, spreading, and subsequent proliferation of human osteoblast-like MG-63 cells to a similar extent, although these values were usually lower than on polystyrene dishes. Nevertheless, the cells on both types of membranes were polygonal or spindle-like in shape, and were distributed homogeneously on the samples. From days 1-7 after seeding, their number rose continuously, and at the end of the experiment, these cells were able to create a confluent layer. At the same time, the cell viability, evaluated by a LIVE/DEAD viability/cytotoxicity kit, ranged from 92% to 97% on both types of membranes. In addition, on PLGA-ND membranes, the cells formed well developed talin-containing focal adhesion plaques. As estimated by the determination of tumor necrosis factor-alpha levels in the culture medium and concentration of intercellular adhesion molecule-1, MG-63 cells, and RAW 264.7 macrophages on these membranes did not show considerable inflammatory activity. CONCLUSION: This study shows that nanofibrous PLGA membranes loaded with diamond nanoparticles have interesting potential for use in bone tissue engineering.
Keywords: Diamond; osteoblasty; viabilita buněk; diamant; Cell Proliferation; Animals; nanofibers; nanočástice; Lactic Acid; tkáňové inženýrství; buněčná adheze; Polylactic Acid-Polyglycolic Acid Copolymer; Nanomedicine; Materials Testing; Humans; Mice; Tissue Engineering; nanomedicína; testování materiálů; kostní náhrady; Bone Substitutes; transmisní elektronová mikroskopie; Nanoparticles; Osteoblasts; mikrofilamenta; nanotechnology; mikroskopie elektronová rastrovací; Microscopy, Electron, Transmission; Nanofibers; proliferace buněk; human bone cells; Cell Adhesion; Cell Line; tkáňové podpůrné struktury; nanovlákna; zvířata; kopolymer kyseliny glykolové a mléčné; Microscopy, Electron, Scanning; electrospinning; kyselina polyglykolová; nanoparticles; Cell Survival; lidé; kyselina mléčná; buněčné linie; Tissue Scaffolds; Polyglycolic Acid; regenerative medicine; myši; Actin Cytoskeleton